Effects of the invasive plant Eupatorium adenophorum on the exotic mealybug Phenacoccus solenopsis (Hemiptera: Pseudococcidae) and their natural enemies. (13th May 2015) - Zhou, Aiming; Bi, Jinqi; Xu, Jianxiong; Wang, Man-Qun
Abstract The mealybug Phenacoccus solenopsis Tinsley and the plant Eupatorium adenophorum Spreng are highly invasive species in China. Previous studies have shown that E. adenophorum is a suitable reservoir for the development of P. solenopsis populations. The natural enemies of P. solenopsis (predator Menochilus sexmaculata and parasitoid Aenasius bambawalei) were infrequently present on E. adenophorum. We hypothesize that E. adenophorum facilitates the colony growth of P. solenopsis by excluding their enemies. We measured the biological parameters of P. solenopsis on E. adenophorum and two cultivated host plants (Gossypium hirsutum and Hibiscus rosa‐sinensis). The results show that, when reared by E. adenophorum, female mealybugs had a shorter developmental duration, greater fecundity, higher survival and larger populations. Compared with cultivated plants, M. sexmaculata experienced lower predatory performance and fecundity on E. adenophorum. Phenacoccus solenopsis also exhibited a lower percentage of parasitism on E. adenophorum. Both predator and parasitoids avoided colonizing the mealybug infested and uninfested E. adenophorum plants in a significant way. These results suggest that E. adenophorum may facilitate the colony growth of P. solenopsis by excluding enemies through their chemical cues.